Analisis Yuridis Terhadap Kawin Lari (NANGKIH) pada Msyarakat Karo Ditinjau dari Undang-Undang Nomor 16 Tahun 2019 Perubahan Atas Undang-Undang Nomor 1 Tahun 1974 - Tarigan, Debby Tri Sebbiana; Sitepu, Runtung; Sembiring, Rosnidar (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Nangkih marriage or elopement in Karo society is a social phenomenon that reflects the complexity between customary law and national law, where this practice was originally a marriage tradition for brides who were not impal (cross-cousin relationships) but is now more often interpreted as a customary solution when there is disagreement from the family. Based on normative-empirical research conducted in Penen Village and Kuala Dekah Village, Sibiru-biru District, Deli Serdang Regency, it was found that Nangkih marriage can still be carried out on condition that it meets the provisions of Law No. 16 of 2019, especially regarding the minimum age limit and marriage registration, where there has been harmonization between the role of customary institutions in ensuring that customary processions continue to run while meeting the formal requirements set by law, although it can have social consequences in kinship relationships when carried out without parental consent